“From zero to three hundred” - intensive acquisition techniques for the 300 most frequent content words in Welsh - Fitzpatrick, Tess; Morris, Steve (Vocabulary Learning and Instruction, 2025)
Around twenty thousand adult learners enrol onto Welsh language classes each year, but many do not progress beyond Mynediad level (= Entry, CEFR A1). The study reported here explored techniques to maintain early learning momentum, maximise learners’ returns for their learning efforts, and accelerate initial vocabulary acquisition. Novice learners of Welsh were challenged to learn 300 Welsh vocabulary items over a period of 50 days. They were provided with physical flash cards and information about learning techniques, and were asked to spend ten minutes per day on their learning. Tests administered immediately after and two weeks after completion of the learning period showed that acquisition success varied considerably between participants, and an end-of-study questionnaire found that the more successful learners had used highly systematic approaches to word selection and revision, and had frequently used the keyword technique of word learning. Test results also revealed that some target words were substantially less successfully acquired than others, and a list of words ranked by “learnability” was compiled. Outcomes from this study are informing curriculum revision by the National Centre for Learning Welsh, the main provider of Welsh language courses for adults. An earlier, Welsh language paper reporting this study was published in the journal Gwerddon (Fitzpatrick & Morris, 2024).